Decomposition of green manure and nutrients release in Subarctic, Kola Peninsula, Russia - G. M. Kashulina; N. V. Chueva; N. I. Litvinova; K. M. Nikerova (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
In the field experiment, the intensity of decomposition and release of nutrients was studied for six types of plant residues – leaves, panicles and straw of oats (Avena sativa), as well as whole plants of lupine (Lupinus angustifolius), phacelia (Phacelia tanacetifolia) and vetch (Vicia sativa) in the arable horizon of Anthrosols on the Kola Peninsula. Samples in mesh nylon bags were sampled after 8, 12 and 24 months of exposure in soil. The loss of weight, the content of Corg and Norg, as well as ash elements – Si, Al, Fe, K, Ca, Mg, P, S and Mn were determined in all plant residue samples. As the results showed, despite the low temperatures, the decomposition of green manure in soil occurred with a high intensity, comparable to the southern chernozem zone: after a year of exposure in the soil, plant residues lost from 47% (oat straw) to 75% (lupine) of their initial ash-free weight. After 2 years, weight loss reached 68% in oat straw and 90% in lupine. The distribution of losses of Corg, Norg, and P between the types of plant residues and decomposition periods correlated significantly (at p≤0.01) with the distribution of weight losses. Changes in the content of other ash elements did not depend on weight loss: depending on the type of material and the stage of decomposition, the samples could not only lose them (K – by all plant residues; Mn – by lupine; S, Ca and Mg – by all plant residues, except straw and oat panicles), but also accumulate them in quantities exceeding the initial ones (Fe – by all species, Mn – by all species except lupine; Ca and Mg – by straw and oat panicles) at certain periods. The accumulation of elements above initial level means that the transformed plant residues can accumulate additional amounts of elements from the soil solution, while the irregular alternation of increases and decreases in Ca, Mg, S, Fe and Mn indicates the reversible nature of the process. Due to the significant differences between the types of green manure in terms of chemical composition, rate and dynamics of decomposition and release of nutrients, their use provides great opportunities for managing soil fertility and the intensity of elements cycling in agrocenoses through the species selection.